Hermansky-Pudlak Syndrome: Identification of Novel Variants in the Genes HPS3, HPS5, and DTNBP1 (HPS-7) - Doris Boeckelmann; Mira Wolter; Katharina Neubauer; Felix Sobotta; Antonia Lenz; Hannah Glonnegger; Barbara Käsmann-Kellner; Jasmin Mann; Stephan Ehl; Barbara Zieger (Frontiers in Pharmacology, 2022)
Hermansky-Pudlak syndrome (HPS), a rare heterogeneous autosomal recessive disorder, is characterized by oculocutaneous albinism (OCA) and a bleeding diathesis due to a defect regarding melanosomes and platelet delta (δ)-granule secretion. Interestingly, patients with HPS type 2 (HPS-2) or HPS type 10 (HPS-10) present additionally with an immunological defect. We investigated three patients (IP1, IP2, and IP3) who suffer from a bleeding diathesis. Platelet aggregometry showed impaired platelet function and flow cytometry revealed a severely reduced platelet CD63 expression hinting to either a defect of platelet delta granule secretion or a decreased number of delta granules in these patients. However, only IP3 presents with an apparent OCA. We performed panel sequencing and identified a homozygous deletion of exon 6 in DTNBP1 for IP3. Western analysis confirmed the absence of the encoded protein dysbindin confirming the diagnosis of HPS-7. Interestingly, this patient reported additionally recurrent bacterial infections. Analysis of lymphocyte cytotoxicity showed a slightly reduced NK-degranulation previously documented in a more severe form in patients with HPS-2 or HPS-10. IP1 is carrier of two compound heterozygous variants in the HPS3 gene (c.65C > G and c.1193G > A). A homozygous variant in HPS5 (c.760G > T) was identified in IP2. The novel missense variants were classified as VUS (variant of uncertain significance) according to ACMG guidelines. For IP1 with the compound heterozygous variants in HPS3 a specialized ophthalmological examination showed ocular albinism. HPS3 and HPS5 encode subunits of the BLOC-2 complex and patients with HPS-3 or HPS-5 are known to present with variable/mild hypopigmentation.